Effect of Agitation, Temperature, and Quenching Medium on Cooling Curve and cooling rate for Steels - Hasan, Hala S.; Khaleefah, Reham H.; Al haboubi, Nasser A.; Salman, Raad D. (Al-Nahrain Journal for Engineering Sciences, 2018)
The control of quenching process has been investigated in this study by developing a quench system design to simulate the quenching process and measure the time – temperature history inside the sample during the cooling stage. The main purpose of this quench system is to evaluate the quench power of different quenchant at different conditions (type, temperature and agitation).A stainless steel sample was used with a suitable measurement as a probe in designing this quench system.The performance of two of quenchants (water and brine) with different conditions was investigated, and the designed probe was used to illustrate the effect of quenching parameters (quenchant type, temperature and its agitation) on cooling curves and cooling rate.The quenching system has proven its ability to work effectively and the results showed that heat transfer properties were significantly affected by quenchant parameters.